Nht1, a Transposable Element Cloned from a Dispensable Chromosome in Nectria haematococca - Jürg Enkerli; Garima Bhatt; Sarah F. Covert (Molecular Plant-Microbe Interactions, 1997)
Certain isolates of the plant-pathogenic fungus Nectria haematococca mating population VI (MPVI) contain dispensable chromosomes that are unstable during sexual reproduction. Several of these chromosomes carry genes for phytoalexin detoxification and thus contribute to the pathogenic potential of this organism. A repeated DNA sequence, Nht1, was cloned from one of these dispensable chromosomes in N. haematococca MPVI. One copy of the repeated element (Nht1A) was completely sequenced. It is 2,198 bp long and it possesses incomplete inverted terminal repeats (ITRs) at each end. Nht1B, a partially sequenced copy of Nht1, has complete ITRs. Nht1A appears to contain 2 introns and encodes a protein of 550 amino acids that is highly similar to the protein encoded by the Fusarium oxysporum transposon, Fot1. Due to the presence of ITRs, its repeated nature, and its similarity to Fot1, we conclude that Nht1 is a transposable element. Within North American N. haematococca MPVI populations, Nht1 is distributed discontinuously. Its copy number in different field isolates varies from zero to approximately 100 copies per genome. The Nht1A source isolate is estimated to contain nine to 11 copies of Nht1; at least six are on the chromosome from which Nht1A was cloned.